Label-Free Infrared Spectral Histology of Skin Tissue Part II: Impact of a Lumican-Derived Peptide on Melanoma Growth - Brézillon, Stéphane; Untereiner, Valérie; Mohamed, Hossam Taha; Ahallal, Estelle; Proult, Isabelle; Nizet, Pierre; Boulagnon-Rombi, Camille; Sockalingum, Ganesh. D. (Frontiers in Cell and Developmental Biology, 2020)
Melanoma is the most aggressive type of cutaneous malignancies. In addition to its role as a regulator of extracellular matrix (ECM) integrity, lumican, a small leucine-rich proteoglycan, also exhibits anti-tumor properties in melanoma. This work focuses on the use of infrared spectral imaging (IRSI) and histopathology (IRSH) to study the effect of lumican-derived peptide (L9Mc) on B16F1 melanoma primary tumor growth. Female C57BL/6 mice were injected with B16F1 cells treated with L9Mc (n=10) or its scrambled peptide (n=8), and without peptide (control, n=9). The melanoma primary tumors were subjected to histological and IR imaging analysis. In addition, immunohistochemical staining was done using anti-Ki-67 and anti-cleaved caspase-3 antibodies. The IR images were analyzed using common K-means clustering to obtain high-contrast IRSH that allowed to identify different ECM tissue regions from the epidermis to the tumor area, correlating well with HE staining. Furthermore, IRSH showed good correlation with immunostaining data obtained with anti-Ki-67 and anti-cleaved caspase-3 antibodies, whereby the L9Mc peptide inhibits cell proliferation and increases strongly the apoptosis of B16F1 cells in this mouse model of melanoma primary tumors.